Book Review. Lloyd, Justine and Ellie Vasta, (eds.). 2017. Reimagining Home in the 21st Century. Cheltenham, Northampton: Edward Elgar Publishing - Łukasiuk, Magdalena (Qualitative Sociology Review, 2018)
-